Reinterpreting the Bulus in the Mihrab of Masjid Agung Demak: Cultural Symbolism, Architectural Sustainability, and Community-Based Conservation - Dian Nafiatul Awaliyah (Department of Architecture, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
The degradation of coastal environments and the loss of cultural identity in heritage architecture due to climate change and urban development have raised concerns about the relevance of traditional symbols in promoting sustainability. In the case of Masjid Agung Demak—Indonesia’s oldest mosque and a spiritual legacy of the Wali Songo—the presence of the bulus (softshell turtle) motif in the mihrab invites deeper reflection on its contemporary significance. This research investigates how the bulus, traditionally viewed as a symbol of balance and resilience in Javanese cosmology, can be scientifically reinterpreted as an ecological and cultural emblem within Islamic architectural heritage. The objective of this study is to explore the potential of the bulus motif to inform regenerative conservation strategies that integrate spiritual symbolism with environmental sustainability. Using a qualitative method that combines architectural semiotics, cultural anthropology, and sustainability discourse analysis, the study identifies the bulus as a nexus of spiritual, ecological, and communal meanings. Findings reveal that the motif is not merely decorative but functions as a biocultural signifier that embodies Islamic-Javanese values of patience, adaptability, and environmental stewardship. Recontextualizing the bulus within sustainability narratives enables a participatory model of heritage conservation that fosters local ecological awareness and reinforces community resilience amid ongoing environmental challenges.